Experimental Assessment of a New Type of Vascular Prostheses with Adiponectin (Adipograft Ra 1Vk 7/350) on Sheep - Jiří Podlaha (Sciendo, 2014)
Despite medical advancements, the development of an ideal vascular prosthesis still poses a great challenge. In this study the researchers tried to test and verify the characteristics of a new type of vascular prosthesis, using adiponectin (Adipograft Ra 1vk 7/350) developed at the Knitting Research Institute, a.s. Brno. Two types of vascular prostheses (12 with adiponectin and 6 as a control without adiponectin) were implanted in nine healthy 4-year-old Merino sheep. The implantation site was the common carotid artery and the length of the implant was 10 cm. We applied the theory of the protected coagulum, whereby all sheep received antibiotics as a prophylactic measure. A Doppler U.S. was performed before finishing each operation, in order to verify the patency of the prostheses. Each animal was followed up during the whole study and the prostheses were extirpated on days 30 and 100 (1 and 3 months). It was observed that all prostheses coated with adiponectin showed patency after extirpation. The lumen implants were of a consistent thickness of 7 mm. Histological study of the implanted prostheses confirmed a quick, high quality, healing. Experimental vascular prostheses coated with adiponectin appeared to be successful in clinical practice. The researchers think that Adipograft Ra 1vk 7/350 can be a turning point in the development of vascular prostheses, due to its patency and quick healing.